2004
DOI: 10.1007/s00421-004-1252-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic ventilatory response is correlated with increased submaximal exercise ventilation after live high, train low

Abstract: This study tested the hypothesis that live high, train low (LHTL) would increase submaximal exercise ventilation (V(E)) in normoxia, and the increase would be related to enhanced hypoxic ventilatory response (HVR). Thirty-three cyclists/triathletes were divided into three groups: 20 consecutive nights of hypoxia (LHTLc, n = 12), 20 nights of intermittent hypoxia (4x5-night 'blocks' of hypoxia interspersed by two nights of normoxia, LHTLi, n = 10), or control (CON, n = 11). LHTLc and LHTLi slept 8-10 h per nigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
3
14
0
1
Order By: Relevance
“…That should contribute to improved exercise tolerance in subjects susceptible to oxygen desaturation, as it is the case in many patients with cardio-respiratory diseases [74]. However, there are only few data available showing that exercise ventilation is increased in normoxia after IH and that this increase is related to the enhanced HVR [51,52]. Townsend et al [52] demonstrated this occurrence in athletes, and we also found indirect indications for it in CAD patients [20].…”
Section: Exercise Tolerance and Ventilationsupporting
confidence: 59%
See 2 more Smart Citations
“…That should contribute to improved exercise tolerance in subjects susceptible to oxygen desaturation, as it is the case in many patients with cardio-respiratory diseases [74]. However, there are only few data available showing that exercise ventilation is increased in normoxia after IH and that this increase is related to the enhanced HVR [51,52]. Townsend et al [52] demonstrated this occurrence in athletes, and we also found indirect indications for it in CAD patients [20].…”
Section: Exercise Tolerance and Ventilationsupporting
confidence: 59%
“…Six or more repeated exposures to relatively severe hypoxia of ≥30 min stimulated HVR [28,35,[44][45][46][47][48][49]. An increased HVR could also be achieved by longer exposures to mild [52,54]. Whereas the effects of IH on exercise ventilation in older people with either cardiovascular diseases or low fitness level are ambiguous [18,20], in patients with mild COPD, a reduction in submaximal exercise ventilation has been observed after IH [27].…”
Section: Ventilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest that long-duration IH (e.g. live high, train low) rather than short-duration IH (*1 h bouts of hypoxia), and prolonged hypocapnic hypoxia is required to alter _ V E during exercise (Townsend et al 2005;Foster et al 2006). …”
Section: Main Findingsmentioning
confidence: 99%
“…Shekerdemian Es folgten teils kontroversielle Studien, die zeigten, dass nicht jeder gleich auf LHTL reagiert [36], das LHTL keinen Einfl uss auf den Lactat Metabolismus im Muskel hat [37], und dass LHTL zu einem verstärktem ventilatorischen response in submaximalen Leistungsebenen führt [38]. Aufgrund unterschiedlicher Methodik und untersuchter Population ergibt sich nur eine sehr geringe Vergleichbarkeit.…”
Section: Schlaf Auf Großer Höheunclassified